The raven, the dove, and the owl of Minerva the creation of humankind in Athens and Jerusalem - Glouberman, M. (Toronto [Ont.] : University of Toronto Press, 2012)
This study presents a substantial revision to received ideas about the relationship between biblical and ancient Greek conceptions of human nature.
Introduction: Athens and Jerusalem -- 1 In Defence of Perplexity -- 2 Man's Estate -- 3 An Ethical Compass -- 4 Raven's Land -- 5 The Reformation -- 6 Contemplating the Bust of Homer -- 7 Nobodies -- 8 The Birth of Death -- 9 Becoming Political -- 10 Love Stories -- 11 Life and Times -- 12 Misbehaviourism -- Conclusion: On the Carmel.
Includes bibliographical references and index.
Keywords: Theological anthropology -- Biblical teaching; Philosophical anthropology -- Greece -- History; Philosophy, Ancient; RELIGION / Christian Theology / Anthropology; Electronic books